2008
DOI: 10.1097/grf.0b013e31816f29ce
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and its Implication for Pregnancy

Abstract: Intimate partner violence (IPV) is a common occurrence in pregnancy and results in an increased risk of adverse outcomes. Homicide may be the most common cause of maternal death. Women who are pregnant and the victims of IPV have high rates of stress, are more likely to smoke or use other drugs, deliver a preterm or low birth weight infant, have an increase in infectious complications, and are less likely to obtain prenatal care. The IPV continues in the postpartum period. Adolescents may be at even higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 65 publications
3
133
0
6
Order By: Relevance
“…Women with symptoms of depression or anxiety have a three to five times higher risk of experiencing partner violence [47]. It is generally assumed that physically violent conflicts in a relationship often persist after the birth of a child and these conflicts, in their turn, have a lasting impact on the development of the child [139]. Women who have experienced violence tend to have a more negative attitude toward pregnancy and more difficulty in bonding with their unborn child than pregnant women who have not experienced violence [140].…”
Section: Correlates Of Depression and Anxiety In Pregnancymentioning
confidence: 99%
“…Women with symptoms of depression or anxiety have a three to five times higher risk of experiencing partner violence [47]. It is generally assumed that physically violent conflicts in a relationship often persist after the birth of a child and these conflicts, in their turn, have a lasting impact on the development of the child [139]. Women who have experienced violence tend to have a more negative attitude toward pregnancy and more difficulty in bonding with their unborn child than pregnant women who have not experienced violence [140].…”
Section: Correlates Of Depression and Anxiety In Pregnancymentioning
confidence: 99%
“…Just recently, international surveys have extended the models for the understanding of factors related to the access and quality of women's adherence to the services, including hostile family environment as a potential obstacle to care provided during gestation; some of them have suggested that women who were victims of family violence used less the healthcare services and delayed prenatal care. 1,8,15,25 Nevertheless, this gap in the knowledge of the process remains, considering that the existing research is predominantly conducted in developed countries and explores the theme in an insuffi cient way. Most studies use inadequate methods to identify violence during gestation and do not appraise the effect of intimate partner violence conditioned to the possible confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, IPVv during pregnancy and postpartum is more common than several maternal health conditions (e.g. pre-eclampsia, placenta praevia) with comparable negative consequences, and yet still IPV remain under-discussed within perinatal care [3,4,31,32]. Most researchers and caregivers agree that perinatal care is an ideal moment to address IPVv, for it is often the only time in the lives of many couples when there is regular contact with health care providers [3,33].…”
Section: Introductionmentioning
confidence: 99%